PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUKAN ALAT PERAGA SEDERHANA TERHADAP HASIL BELAJAR FISIKA PESERTA DIDIK - Yulpi Lorenza; Petri Reni Sasmita; Shabrina Amalia (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2019)
The purpose of this research is to be able to find out the influence of Guided Inquiry learning model assisted by simple teaching aids on physics learning outcomes of students of class XI MIA 12 Kerinci High School. This type of research is an experimental research with the form of Pre-Experimental, One Group Pretest Posttest Design research design. The population in this study were all students of class XI MIA, amounting to 23 students, consisting of 13 female students and 10 male students. Samples were taken by purposive sampling technique sampling by determining the characteristics in accordance with the purpose of the study, so that the sample in this study is all students of class XI MIA, amounting to 23 students. From the learning results obtained from the final test after learning, based on the normality and homogeneity test of the learning outcomes of one class of samples it is obtained that the data are normally distributed and homogeneous, so for hypothesis testing a t-test is used. From the calculation results obtained the average value of the Posttest = 79.43 while the average value of the Pre-test results = 46.70. Because and means rejected and accepted. so it can be concluded that there is an influence of guided inquiry learning model assisted by simple teaching aids on physics learning outcomes of students of class XI MIA 12 Kerinci High School on the concept of static fluid in 2019/2020 school year.